Diversity by design : guide to fostering diversity in the civil engineering workforce - Hatch, Sybil E. (American Society of Civil Engineers, 2008)
Sponsored by Committee on Diversity and Women in Civil Engineering of ASCE With the rapidly changing national demographic, the increasing global competition, and the demand for new talent, the need for diversity in the civil engineering profession has become increasingly important. Diversity by Design: Guide to Fostering Diversity in the U.S. Civil Engineering Workforce provides practical, hands-on suggestions for how to foster, improve, and maintain a diverse and thriving workforce within the civil engineering profession. It highlights the aspects of the current civil engineering workplace that are not conducive to diversity, and then gives suggestions based on lessons learned from individuals and organizations in the profession for how to create a more diverse workplace. Topics include: Diversity: Why It's Important to the Civil Engineering Profession; Roadmap to Diversity; The Diversity Landscape; Retaining Diverse Civil Engineers; Recruiting Diverse Civil Engineers; and Managing a Diverse Workforce. Intended to complement the Guide to Hiring and Retaining Great Civil Engineers (ASCE Manuals of Practice 103), this guide will be valuable to all organizations, associations, and employers involved in the civil engineering profession.
Keywords: Civil engineering -- United States -- Personnel management.; Civil engineers -- United States.; Diversity in the workplace -- United States.; elektronické knihy; electronic books